Green knowledge management and technology for organizational sustainability: The mediating role of knowledge-based leadership - Abeer Hmoud Al-Faouri (Cogent Business & Management, 2023)
In today's business landscape, the integration of green knowledge management and technology has become a crucial element for organizations to meet the emerging expectations of environmentally-conscious consumers. This study aims at examining the impact of green knowledge management, including green knowledge acquisition, storage, sharing, application, creation, as well as technology in organizational sustainability across its economic, social, and environmental dimensions. The data for this research was collected from different industries of IT companies in Jordan operating in IT solutions and services such as the financial services with a sample size of 288 companies. The Structural equation modeling SEM was used to analyze the data. The results indicated a positive effect of green knowledge management on organizational sustainability with an estimate of 0.253 for this relationship. Furthermore, the findings suggest that knowledge-based leadership mediates the relationship between green knowledge management, technology, and organizational sustainability. The research provides useful insights and perspectives for a better understanding of this topic and offers suggestions and implications to cover the gaps in existing research. Overall, this study highlights the importance of implementing green knowledge management and technology in promoting organizational sustainability, which can lead to a competitive advantage, enhanced organizational performance, and increased stakeholder satisfaction.
Keywords: 650; green knowledge management; knowledge-based leadership; organizational sustainability